2022
DOI: 10.1093/aje/kwac011
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of COVID-19 Vaccination, SARS-CoV-2 Infection, and Fertility

Abstract: Some reproductive-aged individuals remain unvaccinated against COVID-19 due to concerns about potential adverse effects on fertility. We examined the associations of COVID-19 vaccination and SARS-CoV-2 infection with fertility among couples trying to conceive spontaneously using data from an internet-based preconception cohort study. We enrolled 2,126 self-identified females residing in the U.S. or Canada during December 2020-September 2021 and followed them through November 2021. Participants completed questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 59 publications
1
70
0
5
Order By: Relevance
“…It is known that SARS-CoV-2 infection in humans is associated with oligo- and azoospermia and a transient decrease in fertility after infection 36, 38, 66, 68, 71, 72 . One study found that fertility amongst infected men was reduced and returned to baseline 3-6 months after SARS-CoV-2 infection 73 . This decrease in fertility was not seen in infected women or men who received a SARS-CoV-2 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that SARS-CoV-2 infection in humans is associated with oligo- and azoospermia and a transient decrease in fertility after infection 36, 38, 66, 68, 71, 72 . One study found that fertility amongst infected men was reduced and returned to baseline 3-6 months after SARS-CoV-2 infection 73 . This decrease in fertility was not seen in infected women or men who received a SARS-CoV-2 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has been associated with several health consequences pertaining to many bodily organs from the lungs to the brain, to others [ 1 , 2 ]. Even though it is well established that the COVID-19 vaccine is safe for reproduction [ 3 ], there have been a lot of theories pertaining to the fact that COVID-19 infection itself could impact male fertility [ 4 ]; however, data confirming this hypothesis are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…40 A prospective study of 2126 women in North America who wished to become pregnant showed that neither infection nor vaccination had any effect on rate of conception per menstrual cycle. 38 There are problems in pregnancy due to COVID-19 that are beyond the scope of this article. It is, at least, reassuring to find that in the first trimester the viability of the fetus in women with COVID-19 is no different to that in uninfected women.…”
Section: Femalesmentioning
confidence: 99%
“…A transient fall in the conception rate has been shown in a prospective study of infected men. 38 More data are required to confirm this effect.…”
Section: Malesmentioning
confidence: 99%